A review of argasid ticks and associated pathogens of China - Chen, Ze; Liu, Jingze (Frontiers in Veterinary Science, 2022)
It has been recorded 218 species of soft ticks in the world. However, the classification system of Argasidae is still unclear with nearly 2/3 controversial species in genus-level. Therefore, it is very necessary to carry out comprehensive researches of soft ticks. In the year of 2016, Wen and Chen for the first time overviewed the valid species of soft ticks in China. Up to now, the soft tick fauna of China remains poorly known. Although several studies have been undertaken, the information soft ticks and tick borne diseases is fragmentary. To facilitate future study of this group, the scattered information on soft ticks of China is synthesized. Towards the end of 2021, the argasid tick fauna of China consists of 15 valid species, of from these, 9 species (60%) including Argas beijingensis Teng, A. japonicus Yamaguti, Clifford & Tipton, A. persicus (Oken), A. sinensis Jeu & Zhu, 1982, A. vespertilionis (Latreille), A. vulgaris Filippova, Ornithodoros lahorensis (Neumann), O. tartakovskyi Olenev and O. papillipes Birula have been recorded biting on humans. A. persicus is the most common species, and its borne pathogens are widely investigated, while most other argasid ticks are not sufficient studied in China. Here we summarize detailed information regarding hosts, geographical distribution, molecular characters, and vector roles of argasid ticks in China.